A compact and grounded comb‐shaped microstrip antenna: A key to realize enhanced radiation performance. Issue 6 (25th February 2017) - Pawar, Major Umesh Ankush; Chakraborty, Subhradeep; Chattopadhyay, Sudipta
Abstract: A compact grounded comb‐shaped single‐element microstrip antenna is proposed with wide beam width and symmetrical radiation pattern in both principal and diagonal planes. The proposed antenna exhibits excellent isolation of around 35 dB between co‐polarized and cross‐polarized radiation while the same for a conventional patch is only 15 dB. Around 105°‐110° of 3 dB beamwidth is achieved in both principal and diagonal (skew) planes at the center frequency. Around 1.5 dB of front‐to‐back radiation isolation is found from the proposed patch. Most importantly, the proposed antenna produces 65% and 35% broader beam in H‐ and E‐planes, respectively, than that of a classical microstrip antenna. Furthermore, in all principal and diagonal planes, the radiation pattern is found to be symmetrical in a wide angular region (−125° to +125°).